Provider and client perspectives on maternity care in Namibia: results from two cross-sectional studies - Jennifer Wesson; Ndapewa Hamunime; Claire Viadro; Martha Carlough; Puumue Katjiuanjo; Pamela McQuide; Pearl Kalimugogo (BMC, 2018)
Abstract Background Disrespectful and abusive maternity care is a complex phenomenon. In Namibia, HIV and high maternal mortality ratios make it vital to understand factors affecting maternity care quality. We report on two studies commissioned by Namibia's Ministry of Health and Social Services. A health worker study examined cultural and structural factors that influence maternity care workers' attitudes and practices, and a maternal and neonatal mortality study explored community perceptions about maternity care. Methods The health worker study involved medical officers, matrons, and registered or enrolled nurses working in Namibia's 35 district and referral hospitals. The study included a survey (N = 281) and 19 focus group discussions. The community study conducted 12 focus groups in five southern regions with recently delivered mothers and relatives. Results Most participants in the health worker study were experienced maternity care nurses. One-third (31%) of survey respondents reported witnessing or knowing of client mistreatment at their hospital, about half (49%) agreed that "sometimes you have to yell at a woman in labor," and a third (30%) agreed that pinching or slapping a laboring woman can make her push harder. Nurses were much more likely to agree with these statements than medical officers. Health workers' commitment to babies' welfare and stressful workloads were the two primary reasons cited to justify "harsh" behaviors. Respondents who were dissatisfied with their workload were twice as likely to approve of pinching or slapping. Half of the nurses surveyed (versus 14% of medical officers) reported providing care above or beneath their scope of work. The community focus group study identified 14 negative practices affecting clients' maternity care experiences, including both systemic and health-worker-related practices. Conclusions Namibia's public sector hospital maternity units confront health workers and clients with structural and cultural impediments to quality care. Negative interactions between health workers and laboring women were reported as common, despite high health worker commitment to babies' welfare. Key recommendations include multicomponent interventions that address heavy workloads and other structural factors, educate communities and the media about maternity care and health workers' roles, incorporate client-centered care into preservice education, and ensure ongoing health worker mentoring and supervision.